METALLURGICAL AND LIFE-TIME ASSESSMENT OF HIGH-PRESSURE (HP) STEAM PIPES OF A PALM OIL PROCESSING PLANT - Adnyana, D.N. (Metalurgi, 2018)
This paper presents a metallurgical assessment performed on HP steam pipes of a newly constructed plant for transporting high pressure steam from a boiler to a palm oil processing plant. The aim was to assure that the material integrity of the steam pipes meet the intended specification and reliability. In addition, the aim was also to determine the estimated service life of the steam pipes. The metallurgical assessment was conducted by preparing a number of specimens from the as-received three pieces of HP steam pipes. Various laboratory examinations were performed including chemical analysis, metallographic examination, hardness testing and tensile testing at 3000C. In addition, a life-time calculation and analysis was also made using an equation based on the ASME Boiler and Pressure Vessel Code (BPVC) and data obtained from the API Standard 530. Results of the metallurgical assessment obtained showed that the HP steam pipes which were made of ASTM A-106 Gr. B were all in good condition, either in microstructure or mechanical property. There were no any significant defect observed, and all the three HP steam pipes were assumed being ready to place in service. Under the intended operating pressure and temperature of 70 bar(g) and 3000C (max), respectively it can be estimated that the HP steam pipes may likely reach some design life up to 25 years or more with the corrosion rate approximately 0.2 - 0.3 mm/year.